Circulating FK506 binding protein 51 mRNA expression in patients with pituitary adenomas. Issue 1 (January 2023) - Yang, Yingying; Babayan, Lilit; Mirzakhanian, Argishty; Sisliyan, Nvard; Zhang, Dongyun; Hurtado, Carolina; Zahid, Abdul; Bergsneider, Marvin; Kim, Won; Wang, Marilene B.; Heaney, Anthony P.
Abstract: Background: FK506 binding protein 51 (FKBP5) is a co-chaperone regulator of the glucocorticoid receptor (GR). Recent studies have reported increased FKBP5 mRNA in the circulation from patients with Cushing disease (CD) which returned to comparable levels seen in healthy controls following successful trans -nasal trans -sphenoidal (TNTS) surgical corticotroph tumor removal. However, the expression of circulating FKBP5 mRNA levels in other pituitary tumor subtypes and its specificity to corticotroph tumors is unknown. Methods: Pre-operative blood was collected from consecutive patients undergoing TNTS for pituitary tumors (n = 57) at our center between 2015 and 2019. Total RNA was isolated from whole blood using RiboPure blood RNA isolation kit and real-time qPCR was used to quantitate circulating FKBP5 mRNA expression. Results: Consistent with the prior report, higher circulating FKBP5 mRNA levels were observed in 20 patients with CD prior to surgical tumor removal, compared to 21 healthy controls (p < 0.0005) and compared to 8 patients harboring gonadotroph pituitary tumors (p < 0.05) and 6 patients with silent corticotroph pituitary tumors (p < 0.05). However, circulating FKBP5 mRNA levels were higher in 10 patients with prolactin (PRL)-secreting pituitary tumors compared to healthy controls (p < 0.05), and did not differ between patients with CD and patients with growth hormone secreting tumors (GH-omas). Conclusions: Although we confirm that circulating FKBP5 mRNA is higher in patients with corticotroph tumors compared to healthy subjects, measurement of circulating FKBP5 does not appear to be helpful to distinguish corticotroph tumors from other pituitary tumor sub-types.